A study on botteleneck operations to optimize manpower planning for productivity improvement at 2HC door lining assembly line via MODAPTS - Nur Amira, Zulkarnain (2013)
This study was performed in order to find optimize manpower planning for productivity improvement at 2HC 1.8 door lining assembly line. MODAPTS or Modular Arrangement of Predetermined Time Standards, which was developed by Mr. G. Chris Heyde, has been used widely in manufacturing field and benchmarking from the success of other well performance company, Johnson Control Incorporation, JCI is taking the initiative to use MODAPTS. MODAPTS system relates standard time value to human body movement in performing a work. In the study, MODAPTS code will be generated based on video taken and line balancing graph will be plotted. Using VSM layout, waste will be identified and this will be followed by improvement activity in order to reduce or eliminate the waste. Once again MODAPTS code will be generated to monitor the impact of the improvements activities carried out. Based on the line balancing graph and efficiency level of the assembly line, suggestion either to combine two different workstation will be made. This will be followed by initiation of MODAPTS code for the suggested activity. In order to make confirmation either the MODAPTS code is reliable enough, time study at the actual assembly line will be carried out.